Eksistensi Calon Perseorangan Dalam Pemilukada di Indonesia - Ronaldo Adhi Perdana; A Salman Maggalatung (STAATSRECHT: Indonesian Constitutional Law Journal, 2019)
Abstract.Every citizen has the right to get the same opportunity in government. Therefore, the state must facilitate the rights of its citizens, because it is regulated in the constitution. This study uses normative legal research methods and literature studies. The results showed that the existence of individual candidates in the political and democratic system occurred because Law No. 32/2004 on Regional Government only limited and facilitated candidates for regional heads who came from political parties only. Individual candidates in the post-conflict local election in Indonesia are insignificant because one of them is the regulation governing individual candidates considered burdensome for individual candidates, even though the individual candidates have been regulated in the 1945 Constitution and strengthened by the Constitutional Court Decision Number 5/PUU-V/2007 which is the political right of the community to be chosen as a form of democracy and human rights. Deparpolization is caused by a decrease in public trust in political parties, so that people look for other political channels and provide space for people who do not have political vehicles, which are expected to be able to answer the deadlock of political parties so that their political rights can run well.Keywords: Individual Candidates, Democracy, Political Parties, General Election.